2021
DOI: 10.3389/fonc.2021.717397
|View full text |Cite
|
Sign up to set email alerts
|

First Line and Second Line Chemotherapy in Advanced Cholangiocarcinoma and Impact of Dose Reduction of Chemotherapy: A Retrospective Analysis

Abstract: ObjectivePrognosis of patients with irresectable cholangiocarcinoma is still poor. The ABC-02 trial established the current first line (1L) standard systemic chemotherapy (CT) with gemcitabine/platinum derivate for advanced cholangiocarcinoma. However, the majority of patients needed therapy adaptions. Thus, the aim of this study was to evaluate 1L and second line (2L) therapy regimens and the impact of therapy adaptions in an unselected real-life cohort of patients with advanced cholangiocarcinoma.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Nevertheless, it must to be highlighted that the baseline characteristics onset of any cancer-specific therapy were similar between the three treatment groups. However, the triple-therapy group received significantly more often a second-line SC and that could positively affect the OS (14,42,43). Potentially, the trend to a longer OS within the triple group might be an indication for summation potential of the beneficial effects of concomitant ePDT and eRFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it must to be highlighted that the baseline characteristics onset of any cancer-specific therapy were similar between the three treatment groups. However, the triple-therapy group received significantly more often a second-line SC and that could positively affect the OS (14,42,43). Potentially, the trend to a longer OS within the triple group might be an indication for summation potential of the beneficial effects of concomitant ePDT and eRFA.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published TOPAZ-1 trial demonstrated the beneficial effect of adding durvalumab to gemcitabine and cisplatin ( 13 ). Under gemcitabine and cisplatin, patients showed a median overall survival (OS) between 11.1 and 12.2 months ( 14 ). The addition of durvalumab to the established regimen improved OS to 12.8 months ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…When curative resection is not possible, palliative systemic chemotherapy remains as standard therapy. To date, most regimes introduce a gemcitabine- and platinum-based therapy as first line, based on the results of the ABC-02 study ( 20 ), followed by a 5-FU doublet combination as second-line (ABC-06) ( 21 , 24 ). In recent years, tumor sequencing as part of the concept of personalized tumor therapy has emerged as a crucial tool.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this regimen could increase resectability only in few patients. In addition, most of patients required dose adaptions[ 28 ]. That forced researchers to seek other systemic agents including targeted therapy to increase survival and as a bridge to curative surgery in advanced disease.…”
Section: Role Of Systemic Chemotherapy In Cholangiocarcinoma Managementmentioning
confidence: 99%